Homines, funera, astra 3-4 : the multiple faces of death and burial : proceedings of the International Symposium on Funerary Anthropology, '1 Decembrie 1918' University (Alba Iulia, Romania) - Kogălniceanu, Raluca; Gligor, Mihai; Soficaru, Andrei; Stratton, Susan (Archaeopress Archaeology, 2023)
The third volume of the Homines, Funera, Astra series gathers works presented at the third and fourth editions of the International Symposium on Funerary Archaeology: Death and Fire in Ancient Times (15-18 September 2013), and Time and Cause of Death from Prehistory to the Middle Ages (21-23 September 2014), both held at the '1 Decembrie 1918' University in Alba Iulia, Romania. The contributions focus on two central topics regarding past funerary behaviour in Central and South-Eastern Europe: cremation, and cause and time of death.